A facile synthesis of trinaphtho[3.3.3]propellane and its π-extension and the formation of a two-dimensional honeycomb molecular assembly1. Issue 18 (4th March 2015) - Kubo, Takashi; Miyazaki, Shogo; Kodama, Takuya; Aoba, Mitsuya; Hirao, Yasukazu; Kurata, Hiroyuki
<x xml:space="preserve">Abstract</x> The multi-gram-scale synthesis of trinaphtho[3.3.3]propellane, its π-extension, and the formation of two-dimensional honeycomb layers were achieved.